A multivariate copula-based SUR probit model: application to insolvency probability of enterprises. (22nd September 2021) - Maneejuk, Paravee; Jaitang, Chalerm; Yamaka, Woraphon
The purpose of this study is to introduce a more flexible joint distribution for a probit model with more than two equations, or a so-called SUR probit model. The main idea of the suggested method is to use a multivariate copula to link the errors of equations in the SUR probit model. We conduct a simulation study to assess the performance of the model and then apply the model to a real economic problem that is the insolvency probability of small and medium enterprises in Thailand. This study considers three economic sectors and speculates some dependencies among them. The results obtained from the copula-based SUR probit model can show a better performance in both simulation and application studies. In addition, it is found to be suitable for explaining the causal effect of the companies' financial statements on their insolvency probability and challenged results for the Thai enterprises are brought out.